Small RNA sequencing highlights potential functions of tsRNAs in regulating pyroptosis in trigeminal neuralgia - Mizhen Qiu; Fei Zeng; Yi Yan; Mu Xu; Xuexue Zhang; Zhijian Wang; Yutong Wang; Daying Zhang; Shibiao Chen (All Life)
The mechanism of pyroptosis in trigeminal neuralgia (TN) progression remains unclear. The discovery of tRNA-derived small RNAs (tsRNAs) in the mechanism of pyroptosis is a breakthrough. We aim to study whether tsRNA is involved in TN progression through pyroptosis. A TN rat model was constructed by chronic constriction injury of infraorbital nerve and then mechanical hyperalgesia was quantitated using a withdrawal threshold test. Mechanical hyperalgesia was significantly elevated by constriction injury. Immunofluorescence revealed that expression of GSDMD and NLRP3 were significantly enhanced in TN rats. The expression of caspase-1, IL-1β, and IL-18 was significantly boosted after TN induction. CoPP + H2O2 exposure induced cell injury and pyroptosis of rat Schwann RSC96 cells, but reversed by VX-765 (a caspase-1 inhibitor). A total of 87 differentially expressed tsRNAs (DEtsRNAs) were identified in TN rats. KEGG pathway enrichment showed that DEtsRNAs were mainly involved in pyroptosis-related pathways, such as MAPK, ErbB, and mTOR signaling pathways. RT-qPCR showed that pyroptosis-related DEtsRNAs of tsRNA003489, tsRNA001840, and tsRNA003424 were downregulated in TN. Network analysis indicated tsRNA003489 and tsRNA001840 interact with NLRP3, a key regulator of pyroptosis. tsRNA has potential to participate in TN progression by targeting pyroptosis-related genes, which provides a new perspective for understanding pathology of TN.